Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) - Sutriningsih, Naning; Pratiwi, Rani; Utami, Bernadhita Herindri Samodera (JURNAL e-DuMath, 2018)
The purpose of this research is to know the difference of mean of mathematics learning result of student applying NHT type cooperative learning model with mean of student learning result of mathematics applying direct learning model. This research uses quasi experimental research method. The population is all of class VIII SMP Negeri Besar in academic year 2016/2017. Sample technique used cluster random sampling technique. The number of samples that follow this research is 108 students. The data were analyzed using nonparametric statistic, Mann Whitney U-test with normal curve approach, because the sample was from non-distributed population. The result of this research are: 1) There is difference of mean of mathematics learning result of student applying cooperative learning model type NHT with mean result of student learning of mathematics applying direct learning model, 2) Average result of student learning of mathematics applying model NHT type cooperative learning is better than the average mathematics learning outcomes of students applying direct learning models.Keywords : NHT, nonparametric statistic, Mann Whitney U-test, learning outcomes